Tackling gambling harm to bingo players at a time of commercial, regulatory and technological change – towards a public health approach. (May 2022) - Maltzahn, K.; Whiteside, M.; Lee, H.; Cox, J.; MacLean, S.
Abstract: Objectives: The aim of this paper is to identify possible regulatory, policy and program measures to address gambling harm to bingo players and their communities, and in doing so extend existing public health approaches to gambling to better include bingo. Study design: This was a qualitative case study of three populations in Victoria, Australia where bingo was popular and structural disadvantage common: Indigenous people in the state's east, Pacific people in the north and older people on low or fixed incomes in the capital, Melbourne. Methods: Our study investigated experiences of bingo, including gambling harm and recommendations for change. Data were generated through interviews with 53 bingo players and 13 stakeholders as well as 12 participant observations of bingo sessions. Results: Five broad drivers of and influences on harm to bingo players are identified: technological, regulatory and commercial changes eroding bingo's protective factors; bingo being used to bolster other forms of gambling; promotion of gambling interests over people's wellbeing; not recognising experiences of different communities and; external structural influences such as racialised poverty. We identify recommendations from bingo players and stakeholders to address harm arising from bingo involving wagering. Based on these recommendations and available evidence, we propose five sets of measures to mitigate against gambling harm to bingo players and their communities, and so extend existing public health approaches to gambling to better encompass bingo. These sets of measures are: safeguarding bingo's protective features; delinking bingo from the gambling eco-system; dismantling political protection of the gambling industry; tailoring strategies for sub-populations and preventing oppression and abuse. Conclusions: In the face of significant regulatory, commercial and technological changes to bingo that risk increasing and intensifying harm, a public health approach to bingo could help mitigate gambling harm.